2013
DOI: 10.1016/j.pec.2013.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Older cancer patients’ information and communication needs: What they want is what they get?

Abstract: To make sure older cancer patients' needs are met, more attention should be paid to the development of interventions supporting both needs assessment and fulfillment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 51 publications
8
51
0
1
Order By: Relevance
“…The findings of this study indicate that the nature and size of the gap between prenatal counseling models and counseling in practice may vary with the assessor, which is in line with conclusions of other research [23,24]. Overall, midwives evaluated their counseling with regards to HE more or less equally congruent relative to clients compared to observers (85% versus 81%).…”
Section: Table 3bsupporting
confidence: 84%
See 2 more Smart Citations
“…The findings of this study indicate that the nature and size of the gap between prenatal counseling models and counseling in practice may vary with the assessor, which is in line with conclusions of other research [23,24]. Overall, midwives evaluated their counseling with regards to HE more or less equally congruent relative to clients compared to observers (85% versus 81%).…”
Section: Table 3bsupporting
confidence: 84%
“…It might also be socially more appropriate for clients to overestimate rather than underestimate midwives counseling, while midwives and clinically removed observers were accurately aware of it. Furthermore, clients might have assessed the counseling from other perspectives than midwives or observers [24]. An explanation for finding high levels of congruence between midwives and observers compared to low levels of congruence between midwives and clients about the topic 'giving advice' might be that midwives experience difficulties to recognize and avoid directive elements.…”
Section: Table 3bmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this perception, nurses should provide the following support to elderly patients with lung cancer: The results obtained in the present study and previous studies conducted in elderly patients, i.e., that elderly patients tend to trust and comply with the information given by health care providers and devise ways to protect their lives from being unduly burdened by side effects suggest that elderly patients with lung cancer will be able to exercise their unique strengths when they communicate well with health care providers and discuss the most appropriate direction of therapy and methods for dealing with side effects. It has been reported that most elderly patients have difficulties communicating with health care providers due to various age-related factors [18]. The subjects of the present study, however, were able to negotiate with their doctors with the help of family members or consulted doctors with the help of a health care provider with whom they shared a closer relationship such as a nurse.…”
Section: Suggestions For Nursing Practicementioning
confidence: 68%
“…Younger patients were more satisfied and found the information given more helpful than older patients ( H3 ), which might derive from less attention so far given to the older cancer age groups regarding informational needs [2224]. Nevertheless, older patients received more written and CD/tape/video information than younger patients.…”
Section: Discussionmentioning
confidence: 99%